Fortalecimiento De La Producción Escrita De Diálogos No Literarios A Través De Las Expresiones Idiomáticas En El Aprendizaje Del Idioma Inglés - Lorena Maribel Yumi Guacho; Enrique Jesús Guambo Yerovi; Carmita Eulalia Rojas Castro; Lara Olivo Lenín Iván (European Scientific Journal, ESJ, 2017)
The purpose of the current research was to strength the production of non-literary written dialogues by using idiomatic expressions in the English- Language teaching-learning process, applied to second level students, class B in the Language Center at Escuela Superior Politécnica de Chimborazo from October 2016 to March 2017. It has been evidenced that the syllabus of the Language Center does not consider the use of idiomatic expressions, so the students acquire neither lexicography nor appropriate vocabulary. This was a correlational, quasi experimental, field trip and documentary research applied to two heterogeneous groups; a control group and an experimental group. The control group developed the traditional contents planned in the institutional syllabus, while the experimental group developed a set of activities as a methodological strategy; a booklet was also designed for being used as a guide by the teachers. Both groups were evaluated through a rubric in two stages: the pre-test and post-test obtaining data to be tabulated, analyzed, interpreted and then compared in order to prove the hypothesis. It was determined that the use of idiomatic expressions strengthens the production of non-literary written dialogues, so it is recommended to apply them in the English language teaching-learning process.